2012
DOI: 10.1097/tp.0b013e318247281b
|View full text |Cite
|
Sign up to set email alerts
|

A New Enzyme Mixture to Increase the Yield and Transplant Rate of Autologous and Allogeneic Human Islet Products

Abstract: Background The optimal enzyme blend which maximizes human islets yield for transplantation remains to be determined. In this study, we evaluated 8 different enzyme combinations (ECs) in an attempt to improve islet yield. The ECs consisted of purified, intact, or truncated class 1 (C1) and class 2 (C2) collagenases from Clostridium histolyticum (Ch) as well as neutral protease (NP) from Bacillus thermoproteolyticus rokko (thermolysin) or Ch (ChNP). Methods We report the results of 249 human islet isolations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 40 publications
2
80
0
Order By: Relevance
“…Previous reports have demonstrated that the insulin-independence rate after AIT is dependent on the mass of transplanted islets (13), and after intrahepatic infusion autologous islets survive better than allogenic islets (12). Despite the improvements made in islet isolation techniques (14) and the absence of an autoimmune response against the islets, achievement of insulin independence among AIT patients is rather poor at about 40% (15).…”
Section: Introductionmentioning
confidence: 94%
“…Previous reports have demonstrated that the insulin-independence rate after AIT is dependent on the mass of transplanted islets (13), and after intrahepatic infusion autologous islets survive better than allogenic islets (12). Despite the improvements made in islet isolation techniques (14) and the absence of an autoimmune response against the islets, achievement of insulin independence among AIT patients is rather poor at about 40% (15).…”
Section: Introductionmentioning
confidence: 94%
“…In the past 6 years, an additional obstacle was introduced into islet isolation research, as the most effective collagenase used in pancreatic digestion (Liberase HI, Roche Pharmaceutics) was removed from the market due to the discovery of an association between the enzyme and an increased risk of spongiform encephalopathy transmission (40). Other collagenases, such as Serva NB1 (Serva, Heidelberg, Germany), Liberase MTF (Roche, Indianapolis, USA) and Vitacyte (CIzyme HA, Indianapolis, USA) (37,(41)(42)(43) are promising alternatives for islet isolation (44). However, studies that have sought to assess which enzyme would be the most adequate for pancreatic digestion have produced conflicting results (40,42,(45)(46)(47)(48).…”
Section: Islet Transplantation and The Current Status Of This Procedumentioning
confidence: 99%
“…Recently, Balamurugan et al 38 evaluated 8 different enzyme combinations in an attempt to improve islet yield. The enzyme combinations consisted of purified, intact or truncated Class I and Class II collagenases from C. histolyticum (Ch) and a NP from Bacillus thermoproteolyticus rokko (thermolysin) or from Ch.…”
Section: Discussionmentioning
confidence: 99%
“…was able to recover the highest islet yield while retaining islet quality. 38 Probably, future comparisons will be made analyzing this new enzyme mixture.…”
Section: Discussionmentioning
confidence: 99%